Analisis Pengaruh Iklim Kerja dan Komitmen Organisasi terhadap Kinerja Pegawai - Yusuf Rahman Al Hakim (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Employees are the greather crucial elemental of quality human resources of an educational institution in achieving national education goals. This achievement requires high employee performance in every training and learning process all education. Employees with high performance are thought to be influenced by the work climate and organizational commitment in an effort to achieve the achievement and quality of teaching as well as the expected quality of learning. The purpose of this study was to examine this relationship at a university in Surabaya as the object of research. The sample was obtained as many as 63 respondents through simple random sampling method and then the data was analyzed in several stages. The results obtained are the results of this study concluded that the formation of employee performance in the field of education has a significant role from the work climate and organizational commitment partially and simultaneously